Loofah mixed fiber scouring cloth and production process thereof

CN122918852APending Publication Date: 2026-10-16GUANGXI GUIMEI TOWEL GOURD DAILY NECESSITIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611394501.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种丝瓜络混合纤维百洁布及其生产工艺,以解决现有工艺中软化不足、处理不均、纤维过度降解、孔隙结构塌陷、成品掉屑及批次稳定性差的问题

Benefits of technology

漆树酶、天然酚类介体与木聚糖酶协同作用于木质素和半纤维素基质,降低纤维束间的刚性约束,维持拉伸强力保留率不低于80%;天然酚类介体扩大漆树酶对木质素结构的作用范围,木聚糖酶提高基质可接近性,能够在40至55℃的条件下完成15至45分钟的酶解处理;采用含氧高湿交替循环送风,使材料含水稳定和氧传递同时得到保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The present application relates to natural fiber materials and cleaning product processing field, specifically to a kind of luffa sponge mixed fiber scouring cloth and its production process;It includes raw material pretreatment, composite enzyme solution application, oxygen-containing high-humidity enzymolysis, wet heat enzyme inactivation elution, segmented drying and mixed fiber web forming step;Process will luffa sponge be applied with composite enzyme solution containing lac enzyme, xylanase and natural phenolic mediator, in oxygen-containing high-humidity bin alternate air supply enzymolysis, saturated steam instantaneous enzyme inactivation and countercurrent washing are carried out, three-stage gradient drying is carried out, finally luffa sponge fiber bundle is mixed with chemical fiber and needled into shape;Its core is to use lac enzyme-mediator and xylanase synergistically, limited degradation lignin-hemicellulose matrix to weaken the rigid constraint of fiber, and combined with segmented drying to maintain three-dimensional pore;The present application does not use strong acid and alkali treatment, solves the problem of luffa sponge brittle fracture particle shedding and pore collapse under the premise of protecting cellulose skeleton, realizes material flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of natural fiber materials, biomass porous materials and cleaning product processing technology, specifically a loofah sponge mixed fiber scouring pad and its production process. Background Technology

[0002] Luffa sponge is a natural vascular bundle network material obtained from mature luffa fruits after peeling, deseeding, and washing. It is mainly composed of cellulose, hemicellulose, lignin, and a small amount of pectin, wax, and water-soluble extracts. Its continuous and interconnected three-dimensional porous structure gives it excellent water absorption, foaming, dust holding, and friction cleaning properties, making it suitable for use as cleaning and scrubbing materials, filter fillers, buffer materials, and composite material skeletons. In untreated loofah sponges, the composite matrix formed by lignin and hemicellulose has a rigid coating and binding effect on cellulose microfibers, resulting in high overall material stiffness and insufficient bending resilience. After repeated wet-dry cycles or stress friction, the material becomes brittle and particles fall off. This problem mainly stems from the rigid constraint of the lignin-hemicellulose matrix, rather than being entirely limited by the crystallinity of cellulose. Existing loofah softening processes mainly include prolonged boiling, strong acid or alkali treatment, oxidative bleaching, and mechanical kneading. While strong acid, strong alkali, and high-intensity oxidative treatments can quickly remove some lignin and hemicellulose, they easily cause a decrease in cellulose polymerization degree, cell wall damage, high mass loss rate, and collapse of the three-dimensional network. Simple boiling or mechanical treatment has problems such as low softening efficiency, uneven treatment, and short effect retention time. In addition, most existing scouring pads use a single chemical fiber web layer, and products that mix loofah fiber bundles with chemical fibers and needle-punch are rare. Summary of the Invention

[0003] The purpose of this invention is to provide a loofah sponge mixed fiber scouring pad and its production process, to solve the problems of insufficient softening, uneven treatment, excessive fiber degradation, pore structure collapse, lint shedding, and poor batch stability in existing processes. To achieve the above objective, the specific technical solution of this invention is as follows: A manufacturing process for a loofah sponge mixed fiber scouring pad includes the following steps: (1) After removing impurities from the loofah sponge, pre-wash it with warm water at 35-55℃ and drain it; (2) Prepare a compound enzyme solution with pH 4.5-5.8 by mixing compound enzyme solution with oven-dried loofah sponge at a mass ratio of 1.5:1-5:1. The compound enzyme solution contains buffer salts, natural phenolic mediators 0.1-2.0 g / L, lacquer tree enzyme 10-100 U / g and xylanase 50-500 U / g (all based on oven-dried loofah sponge). (3) Preheat the compound enzyme solution to 35-55℃ and ensure that the dissolved oxygen reaches saturation of more than 95%, apply it to the loofah sponge and stir it evenly to achieve a liquid coverage rate of 50%-100%; (4) Place it in an oxygen-containing high-humidity chamber and enzymatically hydrolyze it for 15-45 minutes under conditions of 40-55℃, relative humidity of 90%-100%, and oxygen volume fraction of 15%-30% with alternating air supply. (5) Inactivate enzymes in a humid heat medium at 90-105℃ and relative humidity ≥90% for 1-5 minutes, then wash with water at 40-65℃ and pre-dehydrate to obtain loofah sponge material; (6) Perform the following steps in sequence: drying at 38-48℃ and wind speed of 2.0-5.0m / s, drying at 50-65℃ and wind speed of 1.0-3.0m / s, and conditioning and setting at 25-40℃ and wind speed of 0.3-1.5m / s, so that the moisture content reaches 6%-12%; (7) Cut the above materials into fiber bundles, mix them with at least one of polyester (polyester), polyamide (nylon) or polypropylene fibers, and then comb, lay web and needle punch to obtain a loofah mixed fiber scouring pad.

[0004] Overall, this invention uses pre-treated loofah material as an intermediate. First, it is opened to form short loofah fiber bundles. Then, the short loofah fiber bundles are mixed with chemical fibers and sequentially combed, laid, needle-punched and cut to obtain scouring pad fabric. The chemical fibers are preferably polyester fibers or polyamide fibers. Based on the total mass of the short loofah fiber bundles and chemical fibers, the chemical fibers preferably account for 70%-80%, and the short loofah fiber bundles preferably account for 20%-30%.

[0005] Preferably, in step (1), the initial moisture content of the loofah sponge is not higher than 15% on a dry basis; the warm water pre-washing is to spray or rinse with clean water at 35-55℃ for 3-15 minutes; after the warm water pre-washing, it is further treated with a sodium bicarbonate aqueous solution with a mass fraction of 0.05%-0.30% at 35-50℃ for 2-8 minutes, and then washed with clean water until the pH of the effluent is 6.0-7.5.

[0006] Preferably, in step (2), the concentration of the buffer salt is 5-50 mmol / L, and the buffer system is an acetate buffer system or a citrate-citrate buffer system; the natural phenolic mediator is one or more of syringaldehyde, acetylsuccinone, syringic acid, vanillin and vanillic acid; the compound enzyme solution also includes a nonionic wetting agent with a mass fraction of 0.005%-0.05%, and is used within 4 hours after preparation.

[0007] Preferably, in step (3), the liquid carrying rate is 60%-80%, and is calculated according to the following formula: In the formula, P is the liquid carrying rate. The absolute dry weight of the loofah sponge before applying the compound enzyme solution, To determine the quality of the loofah sponge after applying the compound enzyme solution; before applying the compound enzyme solution, the loofah sponge was degassed under vacuum at a gauge pressure of -60 to -20 kPa for 10-60 seconds and then restored to normal pressure. This vacuum degassed and normal pressure reset cycle was repeated 1-3 times.

[0008] Preferably, in step (4), the enzymatic hydrolysis temperature is 45-50℃, the enzymatic hydrolysis time is 20-30min, the relative humidity is not less than 95%, the oxygen volume fraction is 18%-25%, and the circulating airflow speed is 0.2-0.6m / s; the circulating gas is humidified and then sent back to the oxygen-containing high-humidity chamber, and the airflow direction is switched every 1-5min.

[0009] Preferably, in step (4), a diffuse reflection near-infrared probe is used to perform multi-position cyclic scanning, and the scanning bands cover at least two of the following bands: 1400-1500nm, 1650-1750nm, 1850-2000nm and 2200-2350nm. After the scanned data is corrected by scattering, standard normal variable correction and first or second derivative processing, it is input into the partial least squares model. Within the enzymatic hydrolysis time range described in step (4), when the moisture content and lignin modification index output by the model reach the preset threshold, that is, when the moisture content is 96% and the lignin modification index is 0.75, the enzymatic hydrolysis is stopped and the wet heat inactivation of enzyme is triggered. The lignin modification index refers to the ratio of the absolute value of the derivative peak at 2270nm after first derivative treatment to the absolute value of the derivative peak at the same wavelength in untreated loofah sponge. The partial least squares model has 4 latent variables in the moisture content sub-model and 3 latent variables in the lignin modification index sub-model.

[0010] Preferably, in step (5), saturated steam or a steam-hot air mixture at 98-105°C is used for wet heat instantaneous enzyme inactivation, so that the temperature of the loofah sponge center rises to above 85°C and is maintained for at least 60 seconds; After enzyme inactivation, the product is washed using a 2-4 stage countercurrent spray system. The mass ratio of washing water to oven-dried loofah sponge is 3:1-15:1. The washing continues until the pH of the final washing solution is 5.5-7.5 and the conductivity change rate between two consecutive washing solutions is no more than 10%. The conductivity change rate is the ratio of the absolute value of the difference in conductivity between two adjacent washing solutions to the conductivity of the previous washing solution.

[0011] Preferably, in step (5), the pre-dehydration is carried out by one or more of the following methods: low-speed centrifugation, pulse vacuum suction, air knife blowing, or low-pressure light extrusion. The dry basis moisture content of the loofah sponge after pre-dehydration is 100%-200%.

[0012] Preferably, in step (6): the drying step is drying at 38-48℃ and an airflow velocity of 2.0-5.0m / s until the dry basis moisture content is 40%-80%; the drying at 50-65℃ and an airflow velocity of 1.0-3.0m / s until the dry basis moisture content is 8%-15%; the conditioning and shaping at 25-40℃ and an airflow velocity of 0.3-1.5m / s is treatment until the mass change rate between two consecutive weighings is no greater than 1%.

[0013] The present invention also provides a loofah sponge mixed fiber scouring pad, which is made by mixing loofah sponge short fiber bundles with chemical fibers and then carding, web laying and needle punching reinforcement; based on the total mass of loofah sponge short fiber bundles and chemical fibers, the loofah sponge short fiber bundles account for 20%-30% and the chemical fibers account for 70%-80%; the chemical fibers are at least one of polyester fibers, polyamide fibers or polypropylene fibers.

[0014] The beneficial effects of this invention are as follows: The lacquer tree enzyme, natural phenolic mediators, and xylanase work synergistically on the lignin and hemicellulose matrix to reduce the rigid constraints between fiber bundles and maintain a tensile strength retention rate of not less than 80%. The natural phenolic mediators expand the range of action of the lacquer tree enzyme on the lignin structure, and the xylanase improves the accessibility of the matrix, enabling enzymatic hydrolysis to be completed in 15 to 45 minutes at 40 to 55°C. The use of alternating circulation of oxygen-containing and high-humidity air ensures both stable moisture content and oxygen transfer in the material. Detailed Implementation

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1

[0016] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad, which is carried out according to the following steps: 1. Remove the outer skin, seeds, stem, and loose debris from mature loofah sponge raw material with an initial moisture content of 12%. The initial moisture content is calculated on a dry basis. Cut the raw material into 20mm thick slices and spray them in clean water at 45℃ with a liquid-to-solid ratio of 10:1 for 8 minutes. The liquid-to-solid ratio is calculated as the ratio of the mass of the washing water to the oven-dry mass of the loofah sponge. After draining off the surface free water, the pre-washed loofah sponge is obtained. This step removes surface dust, water-soluble impurities, and loose residues, resulting in a stable raw material state that can proceed to the enzyme solution application process. 2. First, prepare an acetate buffer solution at 20 mmol / L and adjust the pH to 5.0. Then, prepare a compound enzyme solution at a ratio of 2:1 between the total mass of the compound enzyme solution and the oven-dry mass of the pre-washed loofah sponge obtained in step 1. Add 40 U / g oven-dry loofah sponge of lacquer tree enzyme, 180 U / g oven-dry loofah sponge of xylanase, and 0.8 g / L of eugenol to the buffer solution to prepare the compound enzyme solution. After heating the compound enzyme solution to 46°C, introduce air bubbles to make the dissolved oxygen reach more than 95% of the air saturation dissolved oxygen at this temperature. In this embodiment, the dissolved oxygen value of clean water after being fully aerated for 30 minutes at the same temperature and pressure was used as the reference value for air saturation dissolved oxygen; the lacquer tree enzyme was purchased from Novozymes, and its activity unit is defined as: the amount of enzyme required to oxidize 1 μmol of 2,2'-adiazon-bis-3-ethylbenzothiazoline-6-sulfonic acid per minute at pH 4.5 and 40°C; Xylanase was purchased from Genentech. Its activity unit is defined as the amount of enzyme required to release 1 μmol of reducing sugar per minute from a 1% xylan solution at pH 5.0 and 50°C. This step puts lacquer tree enzyme, xylanase, and natural phenolic mediators in a reaction solution state to obtain a composite enzyme system that can be directly used for uniform application. 3. Apply the pre-cleaned loofah sponge obtained in step 1 with compound enzyme solution via double-sided ultrasonic atomization. Control the ultrasonic atomization spray flow rate at 50 mL / min and coordinate with roller turning at a speed of 15 r / min to homogenize the liquid and achieve a liquid carry-over rate of 65%. Among them, the liquid carry-over rate is calculated according to the formula calculate, The absolute dry weight of the loofah sponge before applying the compound enzyme solution, To determine the quality of the loofah sponge after applying the compound enzyme solution, the amount of compound enzyme solution to be applied is... The mass of water already absorbed by the pre-washed loofah sponge should be deducted; this step allows the compound enzyme solution to be distributed on the three-dimensional pores and fiber bundle surface of the loofah sponge, resulting in a uniformly liquid-laden loofah sponge to be enzymatically hydrolyzed. 4. The loofah sponge to be enzymatically hydrolyzed obtained in step 3 is sent into an oxygen-containing high-humidity reaction chamber and subjected to compound enzymatic hydrolysis for 25 minutes at 46℃, relative humidity of 98%, and gas phase oxygen volume fraction of 20%. The circulating airflow speed is controlled at 0.4 m / s, and the airflow direction is switched every 2 minutes. This step allows xylanase to perform limited hydrolysis on the xylan-accessible region, and lacquer tree enzyme to perform limited oxidative modification of lignin with the participation of the mediator, resulting in an enzymatic hydrolysis intermediate product with reduced rigidity constraint. 5. Immediately transfer the enzymatic hydrolysis intermediate obtained in step 4 to the moist heat enzyme inactivation process, and treat it with 100°C saturated steam for 3 minutes to make the center temperature of the loofah sponge reach 90°C and maintain it for 2 minutes; this step inactivates lacquer tree enzyme and xylanase, and obtains moist heat enzyme-inactivated loofah sponge with the reaction terminated. 6. The wet heat-inactivated loofah sponge obtained in step 5 is washed with 55℃ warm water in a three-stage countercurrent spray process. The mass ratio of washing water to oven-dried loofah sponge is 8:1. The washing continues until the pH of the final washing solution is 6.4 and the change rate of conductivity between two consecutive washing solutions is less than 10%. The conductivity change rate is calculated as the ratio of the difference in conductivity between two adjacent washing liquid stages to the conductivity of the previous washing liquid stage. In this embodiment, the conductivity of the second and third washing solutions is used for judgment; this step washes out soluble xylose and xylooligosaccharides, low molecular weight lignin products, residual mediators and inactivated enzyme proteins, resulting in a flexible and moist loofah sponge after elution. 7. The flexible, wet loofah sponge obtained in step 6 is subjected to pulsed vacuum suction, maintaining a vacuum of -50 kPa, a pulse cycle of 10 s, and a processing time of 3 min, to perform non-crushable pre-dehydration, reducing its dry basis moisture content to 150%, and controlling the thickness recovery rate to 93% within 1 min after unloading; this step reduces the subsequent drying load and maintains the overall pore shape, resulting in pre-dehydrated loofah sponge; 8. The pre-dehydrated loofah sponge obtained in step 7 is dried in three stages: the first stage is dried at 43℃ and an airflow velocity of 3.5m / s until the dry basis moisture content is 60%; the second stage is dried at 58℃ and an airflow velocity of 2.0m / s until the dry basis moisture content is 11%. The third stage involves conditioning and shaping at 35℃, airflow velocity of 0.8m / s, and inlet air relative humidity of 35%, until the mass change rate is less than 1% after two consecutive weighings, with a time interval of 10 minutes between the two weighings, and the final moisture content is 9%, calculated on a dry basis. This step allows the free water, capillary water, and stress release processes to proceed in stages, resulting in a flexible and porous loofah material. 9. After cutting the flexible porous loofah material obtained in step 8, open it into loofah fiber bundles, and control the length of the fiber bundles to 25mm. This step transforms the loofah material from an overall network into a fiber bundle state that can be mixed with chemical fibers, thus obtaining loofah fiber bundles. 10. The loofah fiber bundles obtained in step 9 are mixed with polyester fibers. The polyester fibers have a fineness of 6 denier, a length of 51 mm, and are three-dimensionally hollow and crimped with a circular cross-section. The two fibers are mixed at a mass ratio of 30:70, carded into a web, cross-laid into 5 layers, needle-punched for reinforcement, and cut. The needle-punching density is 300 needles / cm², the needle-punching depth is 10 mm, and conventional triangular needles are used. The processing speed is 3 m / min, resulting in a loofah mixed fiber scouring pad with a basis weight of 650 g / m². This step enables the flexible porous loofah fiber bundles and chemical fibers to form a stable nonwoven structure, resulting in a ready-to-use scouring pad. Example 2

[0017] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that the natural phenolic mediator in step 2 is replaced by 0.8 g / L of eugenol instead of 0.8 g / L of acetylsuccinone. The remaining steps are the same as in Embodiment 1 and will not be repeated here. Example 3

[0018] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that the natural phenolic mediator in step 2 is replaced by a mixture of 0.4 g / L eugenol and 0.4 g / L vanillin. The remaining steps are the same as in Embodiment 1 and will not be repeated here. Example 4

[0019] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that in step 1, the loofah sponge is cut into cylindrical blanks with an average thickness of 35mm. In step 3, a vacuum-assisted impregnation process is added before applying the compound enzyme solution. That is, a vacuum is drawn for 30s under a gauge pressure of -40kPa, and the compound enzyme solution is sprayed while restoring the normal pressure. This process is repeated twice, and the liquid carrying rate is adjusted to 70%. The remaining steps are the same as in Embodiment 1 and will not be described in detail here. Example 5

[0020] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. Unlike embodiment 1, in step 4, a diffuse reflection near-infrared probe is used to cyclically scan multiple locations. The scanning band covers the absorption regions of 1400-1500nm, 1650-1750nm, 1850-2000nm, and 2200-2350nm. The probe resolution is 8nm. Each measurement point is scanned three times and the average value is taken. A round of cyclic scanning of four fixed measurement points in the chamber is completed every 2 minutes. The scanned data is processed by scattering correction, standard normal variable correction and first derivative processing and then input into the multivariate correction model. When the moisture content and lignin modification index output by the model reach the preset threshold, the enzymatic hydrolysis is stopped and the process proceeds to step 5. The lignin modification index is defined as the ratio of the absolute value of the derivative peak at 2270nm after first derivative processing to the absolute value of the derivative peak at the same wavelength in the untreated loofah. If multiple local peaks appear near 2270nm, the derivative peak with the largest absolute value in the 2250-2290nm range is taken as the peak value. The positive and negative peak directions are not distinguished and are all calculated based on the absolute value. The multivariate calibration model is a partial least squares model. The modeling process is as follows: spectral data of 30 loofah sponge calibration samples with different enzymatic hydrolysis times are collected, and partial least squares regression is performed in combination with the offline measured moisture content and lignin modification index. During spectral acquisition, the distance between the sample surface and the probe window is controlled to be 5 mm. The number of latent variables in the moisture content sub-model is 4, and the number of latent variables in the lignin modification index sub-model is 3. The moisture content threshold is 96%, and the lignin modification index threshold is 0.75 on a dry basis. In this example, the measured time to stop enzymatic hydrolysis is 23 min. The remaining steps are the same as in Example 1, and will not be repeated here. Example 6

[0021] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that the drying temperature in the second stage of step 8 is adjusted from 58°C to 56°C. The remaining steps are the same as in Embodiment 1 and will not be described again here. Example 7

[0022] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that the chemical fiber used for mixing in step 10 is replaced by polyamide fiber instead of polyester fiber. The polyamide fiber has a fineness of 6 denier, a length of 51 mm, a crimp of 15 crimps / 25 mm, and a circular cross-section. The mass ratio of the loofah fiber bundle to the polyamide fiber is 30:70. The remaining steps are the same as in Embodiment 1. Tests showed that the finished scouring pad had a longitudinal breaking strength of 185 N / 5 cm, a wear resistance mass loss of 1.2%, a water absorption rate of 6.5 times its own weight, a fiber particle shedding rate below the detection limit, and a stain removal capacity rating of level 5. Further details are omitted here. Example 8

[0023] This embodiment provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Embodiment 1 is that the chemical fiber used for mixing in step 10 is replaced by polypropylene fiber instead of polyester fiber. In order to control a single experimental variable, the mass ratio of loofah fiber bundle to polypropylene fiber is maintained at 30:70. The remaining steps are the same as in Embodiment 1. Tests showed that the finished scouring pad had a longitudinal breaking strength of 178 N / 5 cm, a wear resistance mass loss of 1.5%, a water absorption rate of 5.8 times its own weight, a fiber particle shedding rate below the detection limit, and a stain removal capacity rating of level 5. Further details are omitted here.

[0024] Comparative Example 1: This comparative example provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Example 1 is that the composite enzyme solution in step 2 does not contain natural phenolic mediators. The remaining steps are the same as in Example 1 and will not be repeated here.

[0025] Comparative Example 2: This comparative example provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Example 1 is that xylanase is not added to the composite enzyme solution in step 2. The remaining steps are the same as in Example 1 and will not be repeated here.

[0026] Comparative Example 3: This comparative example provides a production process for a loofah sponge mixed fiber scouring pad. The difference from Example 1 is that in step 4, the loofah sponge is placed in a closed high-humidity chamber without replenished air, and the volume fraction of gaseous oxygen is maintained at 8% during enzymatic hydrolysis. The remaining steps are the same as in Example 1 and will not be repeated here.

[0027] Comparative Example 4: This comparative example provides a production process for a loofah sponge mixed fiber scouring pad. Unlike Example 1, the wet heat enzyme inactivation process in step 5 is omitted, and the loofah sponge after step 4 directly enters step 6. The remaining steps are the same as in Example 1 and will not be described again here.

[0028] Comparative Example 5: This comparative example provides a production process for a loofah sponge mixed fiber scouring pad. Unlike Example 1, the three-stage drying in step 8 is replaced by a single-stage constant temperature hot air drying, i.e., continuous drying at 60°C and an airflow speed of 2.5 m / s until the final moisture content is 9%. The remaining steps are the same as in Example 1 and will not be described again here.

[0029] Performance Tests and Data Sheets: The flexible porous loofah material obtained in step 8 of each embodiment and comparative example was tested after being placed at a temperature of 23°C and a relative humidity of 50% for 24 hours; the scouring pad product obtained in step 10 was observed after being placed under the same conditions for 24 hours. The tensile strength retention rate was tested according to GB / T24218.3, and samples were taken along the main vascular bundle direction of the loofah sponge. The rate of decrease in bending stiffness was tested in accordance with GB / T18318.1; Moisture content was determined using a 105℃ oven drying method; The thickness recovery rate was calculated by compressing the material to 50% of its initial thickness, holding it for 30 seconds, and measuring the recovered thickness 1 minute after unloading. The overall pore volume retention rate was determined by micro-computed tomography and image analysis, with the pore volume of the loofah before treatment being 100% for conversion. The quality loss rate is calculated based on the difference in oven-dried quality before and after treatment; Residual mediators were determined by high performance liquid chromatography, and the product was expressed as mg / kg of finished product.

[0030] The specific performance test products of each embodiment and comparative example, as well as the processing status of the finished scouring pad, are shown in Tables 1 and 2, respectively: Table 1 Performance test results of each embodiment and comparative example

[0031] Table 2 Processing Status of Finished Scouring Pads

[0032] Even comparing Example 1 (using 0.8 g / L of eugenol with a liquid retention rate of 65%), Example 2 (using 0.8 g / L of acetylsuccine), and Comparative Example 1 (without natural phenolic mediators), it can be seen that after adding natural phenolic mediators, the rate of decrease in bending stiffness increased from 21% to 34%-36%, while the retention rate of tensile strength remained at 88%-90%. This indicates that after natural phenolic mediators participate in the lacquer tree enzyme oxidation cycle, the degree of limited oxidative modification of lignin is improved, the rigid constraints between fiber bundles are weakened, and the flexibility effect is more complete. Comparing Example 1, which used xylanase 180 U / g, with Comparative Example 2, which did not use xylanase, it can be seen that the flexural stiffness reduction rate of Example 1 increased from 24% to 36%, while the overall pore volume retention rate remained at 92%. This indicates that the limited hydrolysis of the xylan-accessible xylan region by xylanase helps to release the bonding constraints of the lignin-hemicellulose composite region without causing substantial degradation of the main load-bearing skeleton. Comparing Example 1 (using 20% ​​oxygen volume fraction) with Comparative Example 3 (using 8% oxygen volume fraction), it can be seen that under high humidity conditions, when only a sealed and moisturized environment is maintained without continuous air supply, the flexural stiffness decrease rate is only 19%, and the residual mediator is 23 mg / kg, which is higher than 18 mg / kg in Example 1. This indicates that the lacquer tree enzyme reaction is significantly affected by oxygen supply. When oxygen is insufficient, the mediator's promoting effect cannot be fully exerted, the degree of lignin modification decreases, the amount of low molecular weight products eluted subsequently is reduced, and the residual mediator is relatively high. Comparing Example 1, which included moist heat enzyme inactivation, with Comparative Example 4, which omitted moist heat enzyme inactivation, it can be seen that the flexural stiffness reduction rate of Comparative Example 4 increased to 47%, but the tensile strength retention rate decreased to 72%, the pore volume retention rate decreased to 80%, and the thickness recovery rate was only 76%. This indicates that if the enzyme is not inactivated in time after enzymatic hydrolysis, hydrolysis will continue to occur during the heating and dehydration process. Although this can further soften the material, it will lead to a decrease in fiber strength, pore damage, and an increase in material shedding rate. Comparing Example 1, which uses three-stage drying, with Comparative Example 5, which uses single-stage 60°C hot air drying, the mass loss rates of the two are similar, at 10.8% and 10.9%, respectively. However, the pore volume retention rate of Example 1 is 92%, which is higher than that of Comparative Example 5 (76%), and the thickness recovery rate has increased from 73% to 90%. This indicates that the material differences do not mainly come from mass loss, but from the different migration modes of free water and capillary water during the drying stage; single-stage constant temperature hot air drying easily causes the surface shrinkage to be faster than the internal shrinkage, resulting in greater capillary shrinkage and deformation accumulation, leading to narrowing of pores and overall warping; after adjusting the temperature and wind speed in stages, the water loss rates of the inner and outer layers are closer, and the pore structure is easier to maintain. Comparing Example 4, which uses thick cylindrical raw material, vacuum-assisted impregnation, and has a liquid retention rate of 70%, with Example 1, which uses sheet-like raw material and has a liquid retention rate of 65%, it can be seen that Example 4, under the condition of thicker raw material, still achieves a 37% decrease in bending stiffness and a 90% retention rate in pore volume. This indicates that vacuum-assisted impregnation helps to expel trapped air in the pores, improves the distribution of enzyme solution inside the thick-walled loofah sponge, and reduces the difference in treatment between the inner and outer layers. A comparison of Example 5, which uses near-infrared endpoint control, and Example 1, which uses fixed enzymatic hydrolysis for 25 min, shows that the tensile strength retention rate and thickness recovery rate of Example 5 are 90% and 91%, respectively, both slightly higher than those of Example 1. This product indicates that when there are differences in the local composition of the raw materials, using moisture content and lignin modification index as the criteria for stopping enzymatic hydrolysis can reduce local over-treatment and result in high consistency of product performance between batches. A comparison of Example 6 (drying at 56°C in the second stage) and Example 1 (drying at 58°C in the second stage) shows that the rate of decrease in bending stiffness is similar for both. However, the pore volume retention rate of Example 6 is 93%, which is 1 percentage point higher than that of Example 1. This indicates that, under the premise of meeting the capillary water removal efficiency, appropriately lowering the temperature in the medium-temperature drying stage can reduce local thermal shrinkage. If the temperature in this stage is further lowered, the drying time will be prolonged and the moisture retention will be increased, which is not conducive to production cycle control. Therefore, there is a suitable range in the medium-temperature range. A comparison of Example 7, which uses polyamide fiber blends, and Example 8, which uses polypropylene fiber blends, with Example 1, which uses polyester fiber blends, shows that the three have little difference in the basic properties of the flexible porous loofah material. This indicates that the core effect of the present invention is mainly determined by the loofah pretreatment process. Different chemical fibers can be used as subsequent web-forming components, and all of them can form a mixed web layer that can be needle-punched and reinforced with the opened loofah fiber bundles. Based on the above products, it can be seen that there is a synergistic effect between the complex system of lacquer tree enzyme, natural phenolic mediator and xylanase, liquid carry-over rate control, oxygen-containing high-humidity enzymatic hydrolysis, wet-heat instantaneous enzyme inactivation, elution and three-stage drying; the complex enzyme system is used to reduce the rigid constraint of the lignin-hemicellulose matrix; the oxygen-containing high-humidity conditions are used to maintain the oxygen and material moisture stability required for the lacquer tree enzyme reaction; Moist heat inactivation and warm water elution are used to block subsequent excessive hydrolysis and remove low molecular weight residues; staged drying is used to maintain the natural three-dimensional pore network; when all processes work together, the loofah material can obtain high flexibility while maintaining tensile strength and pore structure, and can be further opened, blended and needle-punched into scouring pad products.

[0033] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A production process for a loofah sponge mixed fiber scouring pad, characterized in that, Includes the following steps: (1) After removing impurities from the loofah sponge, pre-wash it with warm water at 35-55℃ and drain it; (2) Prepare a compound enzyme solution with pH 4.5-5.8 by mixing compound enzyme solution with oven-dried loofah sponge at a mass ratio of 1.5:1-5:

1. The compound enzyme solution contains buffer salts, natural phenolic mediators 0.1-2.0 g / L, lacquer tree enzyme 10-100 U / g and xylanase 50-500 U / g (all based on oven-dried loofah sponge). (3) Preheat the compound enzyme solution to 35-55℃ and ensure that the dissolved oxygen reaches saturation of more than 95%, apply it to the loofah sponge and stir it evenly to achieve a liquid coverage rate of 50%-100%; (4) Place it in an oxygen-containing high-humidity chamber and enzymatically hydrolyze it for 15-45 minutes under conditions of 40-55℃, relative humidity of 90%-100%, and oxygen volume fraction of 15%-30% with alternating air supply. (5) Inactivate enzymes in a humid heat medium at 90-105℃ and relative humidity ≥90% for 1-5 minutes, then wash with water at 40-65℃ and pre-dehydrate to obtain loofah sponge material; (6) Perform the following steps in sequence: drying at 38-48℃ and wind speed of 2.0-5.0m / s, drying at 50-65℃ and wind speed of 1.0-3.0m / s, and conditioning and setting at 25-40℃ and wind speed of 0.3-1.5m / s, so that the moisture content reaches 6%-12%; (7) Cut the above materials into fiber bundles, mix them with at least one of polyester, polyamide or polypropylene fibers, and then comb, lay web and needle punch to obtain a loofah mixed fiber scouring pad.

2. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (1), the initial moisture content of the loofah sponge is not higher than 15% on a dry basis; the warm water pre-washing is to spray or rinse with clean water at 35-55℃ for 3-15 minutes; after the warm water pre-washing, it is further treated with a sodium bicarbonate aqueous solution with a mass fraction of 0.05%-0.30% at 35-50℃ for 2-8 minutes, and then washed with clean water until the pH of the effluent is 6.0-7.

5.

3. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (2), the concentration of the buffer salt is 5-50 mmol / L, and the buffer system is an acetate buffer system or a citrate-citrate buffer system; the natural phenolic mediator is one or more of syringaldehyde, acetylsuccinone, syringic acid, vanillin and vanillic acid; the compound enzyme solution also includes a nonionic wetting agent with a mass fraction of 0.005%-0.05%, and is used within 4 hours after preparation.

4. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (3), the liquid carryover rate is 60%-80%, and is calculated according to the following formula: ; In the formula, P is the liquid carrying rate. The absolute dry weight of the loofah sponge before applying the compound enzyme solution, To determine the quality of the loofah sponge after applying the compound enzyme solution; before applying the compound enzyme solution, the loofah sponge was degassed under vacuum at a gauge pressure of -60 to -20 kPa for 10-60 seconds and then restored to normal pressure. This vacuum degassed and normal pressure reset cycle was repeated 1-3 times.

5. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (4), the enzymatic hydrolysis temperature is 45-50℃, the enzymatic hydrolysis time is 20-30min, the relative humidity is not less than 95%, the oxygen volume fraction is 18%-25%, and the circulating airflow speed is 0.2-0.6m / s. The circulating gas is humidified and then sent back to the oxygen-containing high-humidity chamber, and the airflow direction is switched every 1-5min.

6. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (4), a diffuse near-infrared probe is used to perform multi-position cyclic scanning, and the scanning bands cover at least two of the following bands: 1400-1500nm, 1650-1750nm, 1850-2000nm and 2200-2350nm. After the scanned data is corrected by scattering, standard normal variable correction and first or second derivative processing, it is input into the partial least squares model. Within the enzymatic hydrolysis time range described in step (4), when the moisture content and lignin modification index output by the model reach the preset threshold, that is, when the moisture content is 96% and the lignin modification index is 0.75, the enzymatic hydrolysis is stopped and the wet heat inactivation of enzyme is triggered. The lignin modification index refers to the ratio of the absolute value of the derivative peak at 2270nm after first derivative treatment to the absolute value of the derivative peak at the same wavelength in untreated loofah sponge. The partial least squares model has 4 latent variables in the moisture content sub-model and 3 latent variables in the lignin modification index sub-model.

7. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (5), saturated steam or steam-hot air mixture at 98-105℃ is used for wet heat instantaneous enzyme inactivation, so that the temperature of the loofah sponge center rises to above 85℃ and is maintained for no less than 60s; After enzyme inactivation, the product is washed using a 2-4 stage countercurrent spray system. The mass ratio of washing water to oven-dried loofah sponge is 3:1-15:

1. The washing continues until the pH of the final washing solution is 5.5-7.5 and the conductivity change rate between two consecutive washing solutions is no more than 10%. The conductivity change rate is the ratio of the absolute value of the difference in conductivity between two adjacent washing solutions to the conductivity of the previous washing solution.

8. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (5), the pre-dehydration is carried out by one or more of the following methods: low-speed centrifugation, pulse vacuum suction, air knife blowing, or low-pressure light extrusion. The dry basis moisture content of the loofah sponge after pre-dehydration is 100%-200%.

9. The production process of a loofah sponge mixed fiber scouring pad according to claim 1, characterized in that, In step (6): the drying step is drying at 38-48℃ and airflow velocity of 2.0-5.0m / s until the dry basis moisture content is 40%-80%; the drying at 50-65℃ and airflow velocity of 1.0-3.0m / s until the dry basis moisture content is 8%-15%; the conditioning and shaping at 25-40℃ and airflow velocity of 0.3-1.5m / s is to process until the mass change rate between two consecutive weighings is no greater than 1%.

10. A loofah sponge mixed fiber scouring pad, characterized in that, It is made by mixing short fiber bundles of loofah with chemical fibers, and then combing, laying web and needle punching for reinforcement; based on the total mass of the short fiber bundles of loofah and chemical fibers, the short fiber bundles of loofah account for 20%-30% and the chemical fibers account for 70%-80%; the chemical fibers are at least one of polyester fiber, polyamide fiber or polypropylene fiber.